A systematic review of photogrammetry as a reliable methodology in gender identification of human skull - da Silva, Juliana Calistro; Strazzi-Sahyon, Henrico Badaoui; Andreo, Jesus Carlos; Spin, Maurício Donalonso; Nunes, Gabriel Pereira [UNESP]; Shinohara, André Luís (Elsevier, 2023)
One of the most important parameters in the identification process in forensic Medicine and Dentistry is the determination of sex through the skull, based on morphological and metric dimorphism. Photogrammetry is an affordable option that allows the reconstruction of position, orientation, shape, and size, allowing the performance of quantitative and qualitative analyzes to identify the sex of the individual. However, there are few systematic reviews in the literature validating whether photogrammetry is a reliable methodology for sexual identification using human skulls. Therefore, the objective of the current systematic review was to validate whether photogrammetry of dry skulls is reliable as a method for calculating sex in human identification. This revision follows the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) and was recorded in the Prospective International Systematic Reviews Registry (PROSPERO) (CRD420223 Systematic Registry) (CRD420223). The inclusion criteria for selecting the studies were based on the PICO question: “Is test photogrammetry reliable as a method for estimating sex in human identification?“. A literature search for studies was performed in the databases MEDLINE Scopus, Web of Science, LILACS, and the Cochrane Library. The Kappa agreement presented an approval level of (k = 0.93). This systematic review analyzed 11 ex-vivo studies published between 2001 and 2021. The risk of bias was considered low in 8 of the studies, and high in 3 studies. Based on this systematic review, it can be concluded that the photogrammetry method is viable and reliable in identifying sexual dimorphism.
Keywords: Forensic anthropology; Photogrammetry; Sexual dimorphism; Skeletal sex determination